ANALISIS KINERJA APARATUR KELURAHAN TAROK DIPO DALAM MEMBERIKAN PELAYANAN KEPADA MASYARAKAT - Urla Serli Putri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the performance of Tarok Dipo Village apparatus in providing services to the community, both from the aspects of timeliness, service quality, apparatus attitudes, and utilization of facilities and infrastructure. The research method used is descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results showed that the performance of the kelurahan apparatus in general had been running quite well, but there were still several obstacles such as limited human resources, less than optimal utilization of information technology, and delays in the process of completing certain administrations. The community generally feels helped by the existence of village services, but expects improvements in terms of speed, transparency, and a more responsive service attitude. Therefore, efforts are needed to improve the competence of the apparatus, the utilization of digital technology, and the strengthening of a work culture that is oriented towards public services.